Consumer purchase intention on sport footwear among generation Y in Padang, Indonesia - Oktarici, Eddo Nanda (2014)
This study is aims to determine consumer purchased intention on Sport footwear among generation Y in Padang, Indonesia. This study provides a comparative description on consumer purchased intention and factors that affected purchased intention between foreign and local sport footwear among Generation Y. From preceding literature, a theoretical framework was developed to show the effect of country of origin, price, brand image, and product design on consumer purchase intention o Foreign and Local sport footwear among generation Y. A number of samples in this study were 260 respondents, and for sampling is by using convenience sampling method.Primary data in this study were obtained from questionnaires, which then conducted an analysis of data obtained in the form of quantitative analysis. Techniques of data analysis used were multiple linear regression analysis. The hypothesis was tested by F test and t test with α = 0.05. Results of the study indicated that only the country of origin and product designs factors that have a significant influence on consumer purchase intention both for foreign and local sport footwear. Whereas, price only have significant effect when consumer decided to purchase local sport footwear. Meanwhile, brand image only have significant effect when decided to intend purchased foreign sport footwear. A comparative description on purchased intention of Foreign and Local sport footwear revealed some similar, and its differences factors that affect the purchase intentions on sport footwear among generation Y in Padang, Indonesia. Implications and future research suggestions are also discussed.